Activate Your Personal Webshooters : Translation and the Marvel Method - Jokinen, Harri (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis examines the traditional style of creating comic books at Marvel Comics known as the Marvel method, a method for creating comics that has heretofore been largely ignored by academia. In the Marvel method, instead of a comic book penciller working from a full script, the writer and penciller combine to create a rough plot for a story. The penciller then creates the art for the story, after which the writer creates the finished dialogue with the help of the penciller‘s margin notes. The focus is on two notable Marvel comic book runs, The Amazing Spider-Man by Stan Lee and John Romita and The Uncanny X-Men by Chris Claremont and John Byrne. Using stylistic analysis, this paper compares the writing style of the two writers with six different Finnish language translations to establish the parameters of translational choices made by the translators, ranging from a very free translation style to a very faithful one. In its extreme form, the writer‘s role in the scripting phase is comparable to the role of the translator. The writer works with the help of the penciller‘s margin notes to create a finished product that may or may not be in accordance with the penciller‘s vision, the same way the translators work with the finished dialogue to create a translation that varies in faithfulness.